A study on the relationship between economic indicators towards stock price finance sector / Mohd Ariff Mahamad - Mahamad, Mohd Ariff (Faculty of Business and Management, 2006)
The study further examines the relationship between economic indicators towards stock price of finance sector. This study was done because of the controversy opinions about the relationship between economic indicators towards stock price finance sector. The sample consists of interbank interest rate, exchange rate and consumer prices index and financial stock prices. The single linear regression analyses are used to analyze the monthly data from 2001 until 2005. The findings of the study ended with a result, which found that there is a significant relationship between interbank interest rate and Singapore dollar exchange rate with financial stock prices. However, a shocking result found that there is no significant relationship between consumer price index with financial stock prices.